(untitled) (Research, Society and Development, 2020)
Objective: to know the factors related to the motivation for blood donation in a blood collection center in a city in the extreme south of Rio Grande do Sul. Methodology: this is a field research, with a qualitative, descriptive and exploratory character. For data analysis, Bardin’s content analysis technique was used. Results: the results showed motivations such as the family example, the need for a friend and the benefits self-reported by the donor to you and the recipient. Most donors have been donating for many years, but none are loyal. There was an average of two donations a year. Some knowledge about the benefits to the recipient of the donated blood was observed, such as the maintenance of his life, however, in contrast to this, regarding the benefits for donors, knowledge was scarce. Conclusion: it is clear that some strategies can be revised by calling the population, to exercise the donation.